Technical Note: An anthropomorphic phantom with implanted neurostimulator for investigation of MRI safety. Issue 8 (25th May 2020) - Yang, Benson; Tam, Fred; Davidson, Benjamin; Wei, Pei‐Shan; Hamani, Clement; Lipsman, Nir; Chen, Chih‐Hung; Graham, Simon J.
Abstract : Purpose: The objective of this work was to design and construct an improved anthropomorphic phantom for use in studying magnetic resonance imaging (MRI) radiofrequency (RF) safety at 3 T related to deep brain stimulation (DBS), and especially the role of DBS lead trajectories. Method: Based on a computer‐aided design including reasonable representation of human features, the phantom was fabricated by three‐dimensional (3D) printing and then fully assembled with a human skull, a commercial DBS device implanted using the surgical standard at our institution, and fiber‐optic temperature sensors embedded in two tissue mimicking solutions (e.g., the heterogeneous setup). Preliminary MRI safety experiments were conducted using turbo spin‐echo (TSE) imaging with the device powered on and powered off. These results were then compared to analogous results for a homogeneous phantom setup that filled the structure with a standard body average solution. Result: Both phantom setups produced temperature increases of ~1.0°C, with a maximum increase of 1.1 ± 0.2°C recorded during imaging of the heterogeneous phantom setup. The preliminary experimental results suggest that improved phantom structures capable of replicating actual DBS lead trajectories may be advisable when conducting DBS‐related MRI safety studies. Conclusion: An anthropomorphic phantom was constructed with promising initial results indicating different DBS lead trajectories and phantom setups may impact temperature elevations along an implanted DBS lead. Although additional work will be necessary to validate its efficacy over conventional phantoms, the anthropomorphic phantom can likely be used in the future to assess different procedures for DBS lead placement, the RF power deposition of MRI protocols applicable to DBS patients, and to validate novel methods to reduce localized heating effects associated with DBS devices, such as parallel RF transmission.